REALISASI MANAJEMEN POAC KURIKULUM PONDOK PESANTREN MODERN AL-MUROZZA DEPOK DALAM MEMBENTUK SANTRI BERJIWA RELIGIUS - Fatia Ainur Rosyida Fatia; Khusnul Hanifah; Marno (Tadbir: Jurnal Manajemen Pendidikan Islam, 2024)
Nowadays there are still many people who consider Islamic boarding schools to be unorganized education. In fact, curriculum management to this day is still classified as implementing an "impromptu" management system. Al-Murozza Modern Islamic Boarding School answers these challenges by implementing curriculum management based on POAC theory on an ongoing basis. The aim of this research is to reveal curriculum management at the Al-Murozza Modern Islamic Boarding School to form students with a religious spirit. This research applies a case study type of research. Data collection techniques are based on interviews, observation and documentation. This research data analysis applies three activity processes, namely data condensation, data exposure, and drawing conclusions. The results of the research prove that the stages of curriculum management include: (1) Planning: developing goals and programs, preparing activity schedules, (2) Organizing: dividing the Islamic boarding school organizational structure, dividing the organizational structure of the curriculum, (3) Implementation: formal education, early education, teaching Al-Qur'an, (4) Supervision: directly (observing the learning process in the classroom, observing the performance of the ustadz/ustadzah) and indirectly (observing statistics on the learning outcomes of the students through the SIPond application).